PENGARUH MOTIVASI INTRINSIK, KREATIVITAS DAN PENGETAHUAN TEKNOLOGI INFORMASI DAN KOMUNIKASI TERHADAP KESIAPAN DIGITALISASI UMKM DI KAVLING DPR SIDOARJO - Isaam Fajar Maulana; Anom Anom; Sri Andayani (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2024)
One of the impacts of the growth of digitalization is the expansion of business operations on ecommerce platforms, especially the growth and development of digital-based businesses that penetrate into wholesale and retail trade and other service industries such as transportation and warehousing. The purpose of this study is to ascertain the impact of Intrinsic Motivation, Creativity and Knowledge of Information and Communication Technology on the Readiness of Digitalization of MSMEs in the Sidoarjo DPR Lot and also for other MSME players so that they can appeal to how important Digitalization is at this time. For the government, which is expected to participate in the Digitalization process in MSMEs throughout Indonesia. This type of research uses a census research method with a sample of 45 MSME players in the Sidoarjo DPR Lot. The findings of this study indicate that partially the intrinsic motivation variable has a negative effect on the readiness of digitalization of MSMEs in the Sidoarjo Dpr Lot, while the creativity and information and communication technology variables have a positive and significant effect on the readiness of digitalization of MSMEs in the Sidoarjo Lot. Overall, the independent variables have a significant effect on the readiness of digitalization of MSMEs in the Sidoarjo Dpr Lot.